Gambling bank behaviour, incentive mechanism, and sanctions: A two-stage model - Isabel Strecker (Journal of Banking Regulation, 2023)
This article analyses the optimal punishment structure set by a regulator in banking markets under asymmetric information. Relying on a theoretical model, we analyse whether a decreasing, constant, or increasing sanction scheme deters potentially repeated offences in banking. We find that an increasing punishment structure is efficient in reducing gambling bank behaviour. This holds if and only if the regulator's detection probability is low or the amount gambled by the bank, if it would cheat, is high. With this paper, we provide justification for the current policy practice.
Keywords: D82; G21; K42; 330; Banking; Excessive risk; Moral hazard; Enforcement; Repeat offenders